2006
DOI: 10.1210/jc.2006-1174
|View full text |Cite
|
Sign up to set email alerts
|

Improved Triglycerides and Insulin Sensitivity with 3 Months of Acipimox in Human Immunodeficiency Virus-infected Patients with Hypertriglyceridemia

Abstract: Acipimox resulted in significant sustained reductions in lipolysis, improved glucose homeostasis, and significant but modest reductions in triglycerides in HIV-infected individuals with abnormal fat distribution and hypertriglyceridemia. Improvement in overall metabolic profile with acipimox suggests a potential clinical utility for this agent that requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 43 publications
3
27
0
1
Order By: Relevance
“…During stage 2 (high insulin dose), lipolysis was totally blocked by insulin, which is most likely the reason for no detectable effect of acipimox on glucose metabolism. The response of R a FFAs to acute acipimox during high-dose insulin is similar to the response of R a FFAs to chronic acipimox (12).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…During stage 2 (high insulin dose), lipolysis was totally blocked by insulin, which is most likely the reason for no detectable effect of acipimox on glucose metabolism. The response of R a FFAs to acute acipimox during high-dose insulin is similar to the response of R a FFAs to chronic acipimox (12).…”
Section: Discussionmentioning
confidence: 63%
“…In other insulin-resistant states (e.g., obesity and type 2 diabetes), increased rates of lipolysis and plasma FFA concentration are related to the degree of insulin resistance (8 -10). Both acute and chronic suppression of lipolysis can improve insulin sensitivity in HIV lipodystrophy (11,12). However, the nature of improved insulin resistance (i.e., whether due to changes in hepatic or peripheral insulin sensitivity) has not been determined, and the molecular mechanism behind FFA-induced insulin resistance is still incompletely understood.…”
mentioning
confidence: 99%
“…The increased levels of FFAs play an important role in the insulin resistance appearing in HALS, and lipolysis inhibition attained through pharmacological means has been reported to ameliorate insulin sensitivity in HALS patients. 105 Similarly to other events already mentioned, activation of lipolysis appears to be due to a complex combination of HIV-1 infection and HAART-mediated events. In fact, enhanced lipolysis has been reported in HIV 1-infected patients irrespective of HAART.…”
Section: The Paradox Of the Common Inflammation Status In Adipose Tismentioning
confidence: 77%
“…10,28 Studies in HIV-positive subjects demonstrated that inhibition of lipolysis by acipimox resulted in a signifi cant reduction in lipolysis and NEFA levels. 29 Furthermore, a recent study using a high-fat meal showed that increased postprandial NEFA levels were associated with insulin resistance (HOMA-IR) and lipoatrophy in HIV-positive subjects. 30 In our study, we observed a dynamic pattern in NEFA levels with a >50% rapid reduction in response to a physiologic meal following a 12-hour fasting period.…”
Section: Discussionmentioning
confidence: 99%